2020
DOI: 10.3390/molecules25061390
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study on Processed Panax ginseng Products Using HR-MAS NMR-Based Metabolomics

Abstract: Panax ginseng is processed to diversify efficacy. Four processed ginsengs containing white ginseng (WG), tae-geuk ginseng (TG), red ginseng (RG), and black ginseng (BG) were analyzed using nuclear magnetic resonance (NMR) spectroscopy for screening overall primary metabolites. There were significant differences in the sugar content among these four processed ginseng products. WG had a high sucrose content, TG had a high maltose content, and BG had high fructose and glucose content. In the multivariate analyses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…In the case of ginseng stored at low temperature for extended periods, the starch is decomposed and converted into free sugar, which is primarily the result of enzyme activity [ 16 ]. In addition, the sugars of protopanaxadiol (PPD) ginsenoside, Rb1, Rb2, Rc, and Rd, and protopanaxatriol (PPT) ginsenoside, Rg1 and Re, are removed by repeated heat treatment during the manufacture of BG, increasing the content of free sugar [ 17 ]. Browning in the heat treatment process of ginseng is an amino-carbonyl reaction, which is caused by a Maillard reaction between sugars and amino acids [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the case of ginseng stored at low temperature for extended periods, the starch is decomposed and converted into free sugar, which is primarily the result of enzyme activity [ 16 ]. In addition, the sugars of protopanaxadiol (PPD) ginsenoside, Rb1, Rb2, Rc, and Rd, and protopanaxatriol (PPT) ginsenoside, Rg1 and Re, are removed by repeated heat treatment during the manufacture of BG, increasing the content of free sugar [ 17 ]. Browning in the heat treatment process of ginseng is an amino-carbonyl reaction, which is caused by a Maillard reaction between sugars and amino acids [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…Identification of metabolites was carried out by matching the mass fragments of the differentially expressed metabolites with those of standard substances in commercially available databases, including NIST, NBS, and a self-established library, with 70% similarity threshold. Multivariate analyses were carried out with SIMCA software (version 14.1, Umetrics, Umea, Sweden) as previously described [ 31 ]. Principal component analysis (PCA) was processed for checking outlier samples, and orthogonal partial least squares discriminant analysis (OPLS-DA) were processed for identification of differentially expressed compounds.…”
Section: Methodsmentioning
confidence: 99%
“…The color of the resulting product is different from that of WG. Several studies [ 66 , 67 ] have indicated that the key saponin compounds of tae-geuk ginseng are PPT (Rh2, Re, Rf, Rh1, and Rg1) and PPD (Rc, Rb2, Rg3, and Rb1). Another study found Re, Rb1, Rb2, Rg2, and Rh1 were the main ginsenosides in TG [ 68 ].…”
Section: Variations In Ginsenoside Compositions Due To Different Pmentioning
confidence: 99%
“…After steaming, the concentrations of ginsenosides Rg2, Rg3, Rh2, and Rh1 in RG are greater than in TG or DG, and the rare ginsenosides Rk1, Rs3, and Rg5 are also present in RG. The present of rare ginsenosides promotes pharmacologically activities more than the above ginsengs [ 67 ].…”
Section: Variations In Ginsenoside Compositions Due To Different Pmentioning
confidence: 99%